STEM Interest, engineering-oriented career identity, and academic self-efficacy on engineering study intention: A SEM analysis among senior high school students - Wasimudin Surya Saputra; Aam Hamdani; Agus Solehudin; Tasma Sucita (Journal of Environment and Sustainability Education, 2025)
Recognizing the critical contribution of the engineering field to national human resource development and innovation, coupled with the existing challenge of low student interest in engineering careers among Indonesian high school students, this study aims to analyze the influence of STEM Interest and Academic Self-Efficacy (ASE) on Engineering Study Intention (ESI) through the mediating role of Engineering-Oriented Career Identity (EOCI). Â Using a quantitative survey approach, data were collected from 695 students participating in the university entrance selection process. Instruments were adapted from prior validated studies and measured on a 1â€“6 Likert scale. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. Based on the processed data, the findings reveal that both STEM Interest and ASE significantly foster the development of EOCI among students (Î² = 0.420 and Î² = 0.425, p < 0.001). In turn, EOCI strongly predicts ESI (Î² = 0.654; p < 0.001). However, the direct effects of STEM Interest and ASE on ESI were non-significant, confirming that EOCI fully mediates the relationship. This indicates that students' motivation and confidence affect their intention to pursue engineering primarily through identity development. The model explains 45.1% of the variance in EOCI and 43.6% in ESI, with satisfactory convergent and discriminant validity and good model fit (SRMR = 0.039, NFI = 0.948). These findings affirm the importance of forming an engineering career identity in supporting students' transition to engineering education. Practical implications include strengthening motivational programs and engineering career exploration from secondary education.